The IMPLEMENTATION OF HOLISTIC LEARNING STRATEGIES: IMPLEMENTASI STRATEGI PEMBELAJARAN HOLISTIK - Messy Messy; Firani Putri; Darul Ilmi (El-Rusyd, 2023)
Holistic learning is a learning approach that builds humans as a whole and intact by developing all human potential which includes social-emotional potential, intellectual potential, moral (character) potential, creativity, and spiritual. The basic concept of holistic learning is learning approach focuses on understanding information and relating it to other topics so that a knowledge framework is built. Holistic learning views humans as a whole, in the sense of humans with their cognitive, affective and behavioral elements. Humans also cannot stand alone, but are closely related to their environment. In holistic learning, the principle is applied students will learn more effectively if all aspects of their personality (mind, body and spirit) are involved in the learner's experience. Holistic learning greatly contributes to increasing students' interest and motivation because holistic learning contains a unity of physical and spiritual education, honing spiritual intellectual (emotional) skills, a unity of practical theoretical educational material, a unity of personal social divine education material. It also does not look at humans from their separate activities in certain parts, but a creature is whole behavior cannot be explained based on activities of parts. Not only through their intellectual potential, but also from their spiritual and emotional potential.